Probing Genuine Multipartite Einstein–Podolsky–Rosen Steering and Entanglement Under an Open Tripartite System - Sun, Wen-Yang; Ding, Amin; Gao, Haitao; Wang, Le; He, Juan; Ye, Liu (Frontiers in Physics, 2022)
Einstein-Podolsky-Rosen (EPR) steering is a peculiar quantum nonlocal correlation, and has unique physical characteristics and wide application prospect. Even more importantly, multipartite steerable states have more vital applications in the future quantum information field. Thus, in this work, we explore the dynamics characteristics of both genuine multipartite steering (GMS) and genuine multipartite entanglement (GME) and the relations of both them under an open tripartite system. Specifically, the tripartite decoherence system may be modelled by that three parties of a tripartite state undergo the noisy channels. The conditions for genuine entangled and steerable states can be acquired for the initial tripartite state. The results show that the decoherence noises can degrade the GME and GMS and even induce its death. Explicitly, the GME and GMS disappear with increasing the decoherence strength under phase damping channel. However, the GME and GMS rapidly decay to death with increasing of the channel-noise factor, and then come back to life soon after in bit flip channel. Additionally, the results indicate that the GMS is born of the GME, but the GME does not imply the GMS, which means that the set of genuine multipartite steerable states is a strict subset of the set of genuine multipartite entangled states. These conclusions may be useful for discussing the relationship of quantum nonlocal correlations (GME and GMS) in the decoherence systems.